Inflammatory Response After Elective PCI and Subsequent Outcomes in Stable Coronary Artery Disease - Yalcin Dalgic; Osman Muhsin Celik; Sadiye Nur Dalgic; Furkan Gencer; Mutlu Can Kabaci; Servet Batit; Aziz Inan Celik; Sabiye Yilmaz; Metin Cagdas; Ayhan Erkol; Burak Turan (Journal of Clinical Medicine, 2026)
Background/Objectives: Inflammation contributes to atherosclerotic progression and may intensify after percutaneous coronary intervention (PCI). In stable coronary artery disease (CAD), whether post-procedural inflammation is prognostically distinct from baseline inflammatory status and post-procedural renal function remains unclear. Methods: We studied 496 consecutive patients with stable CAD undergoing elective PCI. The primary outcome was a composite of death, myocardial infarction, stroke, or repeat revascularization. Post-PCI high-sensitivity C-reactive protein (hs-CRP) and creatinine were measured 18–24 h after PCI. Multivariable Cox models used clinically prespecified covariates, with hs-CRP log-transformed (hazard ratio [HR] per doubling) and additionally adjusted for its pre-PCI level; discrimination was assessed by ROC analysis with bootstrap internal validation. Results: The endpoint occurred in 43 patients (8.7%) over a median follow-up of 10 months. Post-PCI hs-CRP was independently associated with the endpoint after adjustment for pre-PCI hs-CRP, post-PCI creatinine, and albumin (HR 1.43 per doubling, 95% CI 1.05–1.96, p = 0.025), and after further adjustment for angiographic and procedural characteristics (HR 1.54, p = 0.008); pre-PCI hs-CRP was not independent (p = 0.083). Post-PCI creatinine was independently associated in every model (HR 1.16 per 0.1 mg/dL, p = 0.001) and identified a largely non-overlapping high-risk group. Conclusions: After elective PCI in stable CAD, post-PCI hs-CRP was independently associated with adverse outcomes and provided prognostic information beyond baseline hs-CRP and procedural characteristics in the fitted models, rather than merely reflecting baseline inflammatory status. Post-PCI renal function was a complementary, largely independent risk signal.